Mengevaluasi Efektivitas Pelaksanaan Program Kota Tanpa Kumuh (Studi Kasus pada Wilayah Kota Langsa) - Safrizal, Safrizal; Safuridar, Safuridar; Fuad, Muhammad (Jurnal Samudra Ekonomi dan Bisnis, 2021)
Population growth and development can lead to excesses for the emergence of slum areas, which are often seen as a potential problem in urban areas. To reduce the problems of housing and slum areas, one of the government programs is the City Without Slum (in Indonesia called KOTAKU) program. This study aims to analyze the effectiveness of the program in Langsa City and identify the inhibiting factors of this program. 166 respondents were all village chiefs in Langsa City, community members who were directly or indirectly involved in the program, as well as other stakeholders. Primary data were collected through a questionnaire. The effectiveness evaluation is calculated using the mean value as a percentage of each indicator. The results found that the KOTAKU program was considered effective as an effort to reduce slum settlements in Langsa City. However, several factors were identified that were the main obstacles in the implementation of the program.